External Project Evaluation: A case of RYE Connect - Mwakoi, Violet Shighi (Kajaanin ammattikorkeakoulu, 2017)
Rural Youth Entrepreneurship Connect (RYE Connect), is an international entrepreneurship project, spanning between Finland, Greenland and Ireland. The main objective of this project is to make the Northern Periphery and Arctic region more attractive by supporting entrepreneurship activities among the youth. These activities will in turn create job opportunities in the affected regions. By evaluating this project, project management theories could be related to practice. In this thesis, the whole concept of project management was examined. More emphasis was placed on the project evaluation because, it is important for the project team to know how well or bad they are doing at every stage of the project so that necessary adjustments can be implemented, in order for the project to achieve its intended objectives. In summary, the role of good project management was evidently invaluable in the project. Strong leadership enabled RYE Connect project to move forward even in the face of conflicts among the partners due to cultural differences, delay in funds and even managing change in the project. However, the role of culture in the project, especially in multicultural project teams should be addressed from the start of the project to avoid any miscommunication and to ensure that, everyone in the project is speaking in the same voice regardless of which country they come from. This will avoid conflicts and in turn save time, an extremely important, yet scarce resource in projects.